Pendidikan Anak menurut Lukman Al Hakim - Mochamad Syaifudin (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2017)
Islam is a religion what of kamil, already to insert various concept and to line form up in various problem which to give audience human. All everything what formed conceptual and appearance in the direction of operational can to find and to practice from two-source education is Al-Qur’an and Al Sunnah. Such again family problem with all problematic already to discuss in second source mentioned, so that when to speak about child education to follow Luqman Al Hakim of course this is one labour for to dig up far off what perspective Islam to discuss problem of education in family area. In essence family to from place which first and important for child to get education. Child is form blessing gift Allah which very big. They are not only darling and darling family, but also form goods entrusted to Allah, which must waked and saved. That is why process child education happened every day in family area, so process this time of the day as to give influence which very big to attitude, behaviour, and child personality. In Al Qur’an found many theories which to content principles which to concern activity education like what to doing Luqman Al Hakim in to educate his child. He is a pious man who all capable, so that blessing in sight what to stick to self which to cause he to get title Al Hakim. What is more that, his name and how he to educate his child to one of which monumental because to eternal by Allah Swt in Al-Qur’an.